2017
DOI: 10.1093/nar/gkx089
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of cancer common and specific driver gene sets

Abstract: Cancer is known as a disease mainly caused by gene alterations. Discovery of mutated driver pathways or gene sets is becoming an important step to understand molecular mechanisms of carcinogenesis. However, systematically investigating commonalities and specificities of driver gene sets among multiple cancer types is still a great challenge, but this investigation will undoubtedly benefit deciphering cancers and will be helpful for personalized therapy and precision medicine in cancer treatment. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 70 publications
0
38
0
Order By: Relevance
“…With rapid advances in high-throughput sequencing technologies, some large-scale cancer genomics projects, such as The Cancer Genome Atlas (TCGA) [1] and International Cancer Genome Consortium (ICGC) [2], have produced different omics data including a rich dataset of whole-exome and RNA sequence data [3,4], which provides chances to allow us to accurately infer tumorspecific alterations [5] and help in precision medicine in cancers treatment [6,7]. However, many of genetic changes represent neutral variations that do not contribute to cancer development which are called passenger mutations [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…With rapid advances in high-throughput sequencing technologies, some large-scale cancer genomics projects, such as The Cancer Genome Atlas (TCGA) [1] and International Cancer Genome Consortium (ICGC) [2], have produced different omics data including a rich dataset of whole-exome and RNA sequence data [3,4], which provides chances to allow us to accurately infer tumorspecific alterations [5] and help in precision medicine in cancers treatment [6,7]. However, many of genetic changes represent neutral variations that do not contribute to cancer development which are called passenger mutations [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is a co-occurrence of common MDPs and individual-specific MDPs [74,78]. Hoadley et al [89] found similarity among driver gene sets across distinct cancer types.…”
Section: Multi-mutations In Cancer: Cancer Genes Cancer-driving Protmentioning
confidence: 99%
“…According to Zhang and Zhang [78] genes (N= 2-11) necessary to convert a single normal cell into a cancer cell [77].…”
Section: Multi-mutations In Cancer: Cancer Genes Cancer-driving Protmentioning
confidence: 99%
“…Maximization of the weight function is defined as the maximum weight submatrix problem, which is originally solved by Markov Chain Monte Carlo (MCMC) method [12], and then addressed by an exact binary linear programming (BLP) model [13]. Zhang et al [14] proposed two optimization models to de novo separately discover common driver gene sets among multiple cancer types (ComMDP) and specific driver gene sets of a particular cancer (SpeMDP). However, these methods focus on single pathways or modules [12]- [14], they can not clarify how various cellular and physiological processes are coordinately altered during the initiation and progression of cancer.…”
Section: Introductionmentioning
confidence: 99%